2010
DOI: 10.1007/s12558-010-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Projet de lutte contre le cancer du col utérin à Brazzaville: acquis et perspectives

Abstract: Reçu le 4 janvier 2010 ; accepté le 5 mai 2010 © Springer-Verlag France 2011Résumé L'Organisation mondiale de la santé (OMS) prévoit dans les pays en développement une augmentation de 100 % du nombre de cancers d'ici un quart de siècle environ. Au Congo, depuis 2000, un projet pilote de lutte contre le cancer du col utérin est en cours d'exécution. Ce travail a pour but de présenter les résultats anatomocliniques dudit projet et d'envisager les perspectives de la lutte contre le cancer du col de l'utérus au Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…We enrolled 182 patients with a mean age of 50 years. Our results corroborate those reported by some authors (1-4) but are higher than those found by others (5)(6)(7)(8) showing that ages varied between 45 and 48.3 years. However, the mean age remains lower than that reported by one author (6) in Germany, which was 57.3 years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We enrolled 182 patients with a mean age of 50 years. Our results corroborate those reported by some authors (1-4) but are higher than those found by others (5)(6)(7)(8) showing that ages varied between 45 and 48.3 years. However, the mean age remains lower than that reported by one author (6) in Germany, which was 57.3 years.…”
Section: Discussionsupporting
confidence: 92%
“…More than 70% of breast cancers in sub-Saharan Africa are diagnosed at a late stage due to delayed access to quali ed personnel, reducing the chances of cure and survival (3,4). And the Congo is no exception, as this scourge is also the leading cause of cancer in women, ahead of cervical cancer (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation